Assessment of clinical studies evaluating combinations of immune checkpoint inhibitors with locoregional treatments in solid tumors. (October 2022) - Bertaglia, Valentina; Petrelli, Fausto; Porcu, Michele; Saba, Luca; Pearce, Josie; Luciani, Andrea; Solinas, Cinzia; Scartozzi, Mario
Abstract: In the last decade, immunotherapy with immune checkpoint inhibitors (ICIs) has changed the therapeutic algorithm of cancer patients. ICIs combined with other therapeutic options, such as chemo- and targeted therapies, generate impressive results in cancer patients. Locoregional treatments (LRTs) play an important role in the management of various solid tumors (e.g., hepatocellular carcinoma (HCC), neuroendocrine tumors, etc.), and this therapeutic approach may enhance the activity of the immune response to tumor cells destroying primary tumors and leading to the release of several soluble molecules. This systematic review was performed to identify studies reporting objective response rate (ORR) and survival information in patients with solid tumors treated with ICIs plus LRTs. In the present work, fourteen studies were included, and the majority of them (five studies) enrolled patients with hepatocellular carcinoma (HCC), whereas the others included patients with different diseases. The highest ORRs were seen in HCC (67%, Y-90 RE plus ipilimumab and nivolumab) and melanoma (38%, dendritic cells with mRNA p lus ipilimumab) patients. ORRs were not observed in liver metastases from melanoma and colorectal cancer. These data suggest that combination of ICIs and LRTs is feasible and more active in primary tumors (particularly HCC) than metastases with a synergistic effect on antitumor immunity. However, further studies are needed to better select patients, schedules, and setting of treatments. Highlights: Assessment to evaluate clinical trials that tested immuno- and locoregional therapies in cancer patients with solid tumors. Preclinical studies have shown a synergistic effect between these two therapeutic options. This analysis showed the highest objective response rate in hepatocarcinoma and melanoma. Objective response rate was not observed in liver metastases from melanoma and colorectal cancer.